Evaluation of TCR γ/δ T cells in the lysis of renal tumor cells - Viey, Emilie; Fromont, Gaelle; Chouaib, Salem; Escudier, Bernard; Caignard, Anne (Contemporary Oncology/Współczesna Onkologia, 2005)
The objective of the present study was to evaluate the cytotoxic immune response mediated by the TCRγ/δ T cells population in clear cell metastatic renal cell carcinoma. TCRγ/δ T cell represent 1-10% of peripheral T lymphocytes in human and the majority express a Vγ9Vδ2 TCR rearrangement. They recognize low molecular weight molecules derived from bacterial extracts (phosphoantigen, aminophosphates, alkylamines) without MHC restriction and do not require antigen presentation. They mostly express a memory phenotype (CD45RO, CD95+) and produce IFN-γ and TNF-α in response to mycobacteries or undefined antigen present on tumor cells, indicating their crucial role in the innate and adaptative immune response. In the present study, we evaluate their capacities to lyse primary renal tumor cells and characterize the mechanisms involved in their lytic function.